2018
DOI: 10.7759/cureus.2453
|View full text |Cite
|
Sign up to set email alerts
|

Gram-Negative Pyomyositis in an Immunocompetent Patient

Abstract: Pyomyositis is an acute or sub-acute primary infection of the striated muscles. It is commonly misdiagnosed in its early stages due to its nonspecific presentation and lower suspicion among physicians when it comes to diagnosis. It has been historically associated with tropical climates but is being seen with increasing incidence in temperate regions. In both tropical and temperate areas, Staphylococcus aureus is the most common causative organism; gram-negative organisms are rare and traditionally only seen i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…( 2017 ) reported thigh pyomyositis caused by group A Streptococcus in an immunocompetent adult without any underlying cause, and Knees et al. ( 2018 ) reported Gram‐negative pyomyositis in an immunocompetent patient. Elzohairy ( 2018 ) reported primary pyomyositis in 15 children and concluded that primary pyomyositis can occur in individuals of all ages.…”
Section: Discussionmentioning
confidence: 99%
“…( 2017 ) reported thigh pyomyositis caused by group A Streptococcus in an immunocompetent adult without any underlying cause, and Knees et al. ( 2018 ) reported Gram‐negative pyomyositis in an immunocompetent patient. Elzohairy ( 2018 ) reported primary pyomyositis in 15 children and concluded that primary pyomyositis can occur in individuals of all ages.…”
Section: Discussionmentioning
confidence: 99%